Comparison of the Accuracy of IOL Power Calculation Formulas for Pediatric Eyes in Children of Different Ages - Jiaojiao Kou; Pingjun Chang; Lei Lin; Zhangliang Li; Yana Fu; Yun-e Zhao (Journal of Ophthalmology)
Purpose. This study aims to compare the accuracy of five intraocular lens (IOL) power calculation formulas (SRK/T, Hoffer Q, Holladay 1, Haigis, and Holladay 2) for pediatric eyes in children of different ages. Methods. In this prospective study, patients who received cataract surgery and IOL implantation in the capsular bag were enrolled. We compared the calculation accuracy of 5 formulas at 1 month postoperatively and performed subgroup analysis with the patients divided into three groups according to their ages at the time of surgery as follows: group 1 (age ≤ 2 years, 35 eyes), group 2 (2 years < age < 5 years, 38 eyes), and group 3 (age > 5 years, 29 eyes). Results. 75 patients (102 eyes) were enrolled in this study. The Haigis formula got the smallest PE among all formulas in all three groups. With regard to APE, there were no statistical differences among the formulas except group 2, with the SRK/T formula a little smaller, the Holladay 2 formula a little larger in group 1, and the Haigis formula a little smaller in group 3. In group 2, the Haigis formula had the lowest APE (0.87 ± 0.61 D), while the Holladay 2 formula had the largest (1.71 ± 1.20 D, p<0.001), followed by the Holladay 1 formula (1.51 ± 1.07 D, p=0.002). On comparing the percentage of APE within 0.5 D and 1.0 D obtained with 5 formulas in each group, there were no statistical differences. The SRK/T formula and the Holladay 1 formula showed the highest percentage (40.00% and 60.00%) in group 1. While the Haigis formula got the highest percentage in less than 0.5 D (34.21%) and less than 1 D (60.53%) in group 2. In group 3, the Holladay 2 formula and the Haigis formula got the highest percentage less than 0.5 D (58.62%) and less than 1 D (79.31%). The multiple linear regression indicated that the age at the time of surgery was a significant factor affecting the accuracy of APE; after removing the age, AL was the only factor that affected the accuracy of APE. Conclusion. The SRK/T and the Holladay 1 formulas were relatively accurate in patients younger than 2 years old, while the Haigis formula performed better in patients older than 2.